Hypothyroidism in a patient with non-alcoholic fatty liver disease. (6th January 2011) - Gardner, CJ; Richardson, P; Wong, C; Polavarapu, N; Kemp, GJ; Cuthbertson, DJ
Abstract : Consider hypothyroidism as a cause of non-alcoholic fatty liver disease